1989
DOI: 10.1063/1.343520
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for high-efficiency GaAs solar cells fabricated on Si substrates

Abstract: This paper describes some recent developments in GaAs thin-film solar cells fabricated on Si substrates by metalorganic chemical vapor deposition and numerically analyzes them.GaAs solar cells with efficiency of more than 18% are successfully fabricated on Si substrates by reducing the dislocation density. Photovoltaic properties of GaAs/Si cells are analyzed by considering the effect of nonuniform dislocation distribution on recombination properties of GaAs thin films on Si substrates. Numerical analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…where τ d is one associated with the dislocation density, derived from solving the one-dimensional continuity equation for the transport of minority carriers to the dislocations by Yamaguchi et al [5,20] as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where τ d is one associated with the dislocation density, derived from solving the one-dimensional continuity equation for the transport of minority carriers to the dislocations by Yamaguchi et al [5,20] as follows:…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in refs. [19,20], TD propagates through all layers Table 1 Material parameters used for simulating Ga 1−x In x P, Ga 1−y In y As and Ge subcells, respectively …”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the limiting mechanism for these devices is TDD-based recombination. In support of this idea, many researchers, such as Yamaguchi et al [8], have suggested that better results can only be attained by improving the TDD.…”
Section: Introductionmentioning
confidence: 90%
“…Initial research using this technique at NTT Electrical Communications Lab [7,8] reported that increasing the thickness of a GaAs buffer layer decreased the TDD. These researchers demonstrated a best device that offered a W oc of 0.51 V with a TDD as low as 4:0 Â 10 6 cm À 2 measured via etch-pit density (EPD) and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…This degradation in lifetime may significantly impede the cell performance [4]- [6]. The effective minority carrier lifetime (τ n or τ p ) in a latticemismatched system varies as a function of TDD (f (τ TDD )) [7], [16] and can be expressed as, where τ°p and τ°n are the minority carrier lifetime for a dislocation free material. The τ TDD is the minority carrier lifetime associated with the recombination at dislocation which can be expressed as,…”
Section: Simulation Modelmentioning
confidence: 99%